Disaster Risk Reduction Community Resilience and Responses - Zutshi, Bupinder; Ahmad, Akbaruddin; Srungarapati, Ananda Babu (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book discusses the interconnected, complex and emerging risks in today's societies and deliberates on the various aspects of disaster risk reduction strategies especially through community resilience and responses. It consists of selected papers presented at the World Congress on Disaster Management, which focused on community resilience and responses towards disaster risk reduction based on South Asian experiences, and closely examines the coordinated research activities involving all stakeholders, especially the communities at risk. Further, it narrates the experiences of disaster risk-reduction in different communities that have policy implications for mitigation of future disaster risks in the societies affected by these types of disasters. Written from the social science perspective to disasters rather than an engineering approach, the book helps development and governance institutions to prioritize disasters as a problem of development rather than being parallel to it.